BUILDING A CREATIVE ECOSYSTEM: AN ANALYSIS OF THE IMPACT OF COLLABORATION AND BRANDING STRATEGIES AMONG PIDIE JAYA MSMES AT THE KABI EXPO EVENT - Zulfan (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic pillar of the Indonesian economy, yet they often face classic challenges such as limited market access, capital, and branding capabilities. Exhibitions like the KABI EXPO in Pidie Jaya serve as a strategic intervention to address these challenges and encourage creativity-based local economic growth. This study aims to analyze the impact of collaboration and branding strategies implemented by participating MSMEs and explore the role of KABI EXPO in building a creative ecosystem in the Pidie Jaya region. Using a qualitative approach with a case study design, data were collected through in-depth interviews and participant observation with key informants, including presenters and committee members, as well as 11 participating MSMEs. The data analysis techniques used were descriptive and thematic analysis (Sugiyono, 2012; Sari & Agustina, 2021). The results showed that KABI EXPO successfully facilitated various forms of informal collaboration, such as cross-promotion and knowledge exchange, which directly impacted business network expansion and innovation potential. Furthermore, the exhibition served as a platform for MSMEs to test and strengthen their branding strategies, both visually (packaging and logos) and non-visually (direct interaction and social media adoption). Overall, these findings underscore that KABI EXPO serves as more than just a sales platform. It acts as a catalyst, planting the seeds of a creative ecosystem through collaboration, knowledge exchange, and brand strengthening. The event's success lies not only in its immediate sales boost but also in building a strong foundation for the sustainability and competitiveness of MSMEs in Pidie Jaya.